2015
DOI: 10.25077/jka.v4i3.385
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Resistensi Insulin dengan Gambaran Klinis Sindrom Ovarium Polikistik

Abstract: Abstrak Sindrom Ovarium Polikistik (SOPK) merupakan kelainan endokrin dan metabolik pada wanita usia reproduksi. SOPK merupakan kumpulan gejala dari amenore, oligomenore, infertilitas, obesitas, hirsutisme, acne, alopesia, dan akantosis nigrikan. Resistensi insulin diyakini sebagai salah satu penyebab tersering dari SOPK melalui berbagai mekanisme. Tujuan penelitian ini adalah untuk mengetahui hubungan resistensi insulindengan gambaran klinis SOPK. Penelitian ini dilakukan pada pasien SOPK dengan menggunakan s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
3
10
0
2
Order By: Relevance
“…This is in accordance with the study conducted by Wahyuni et al which stated that the age group with the highest prevalence of PCOS is between age 21-30 years old. 7 The mean BMI in this study was 24.78 kg/m2 and almost 80% of the subjects in this study had a waist circumference above the threshold criteria for metabolic syndrome. These results are similar to the study conducted by Musmar et al showed that the mean BMI and waist circumference of patients with PCOS were 23.37±3.85 kg/m2 and 80.08±7.69 cm, respectively.…”
Section: Discussionmentioning
confidence: 52%
“…This is in accordance with the study conducted by Wahyuni et al which stated that the age group with the highest prevalence of PCOS is between age 21-30 years old. 7 The mean BMI in this study was 24.78 kg/m2 and almost 80% of the subjects in this study had a waist circumference above the threshold criteria for metabolic syndrome. These results are similar to the study conducted by Musmar et al showed that the mean BMI and waist circumference of patients with PCOS were 23.37±3.85 kg/m2 and 80.08±7.69 cm, respectively.…”
Section: Discussionmentioning
confidence: 52%
“…The results of this study are in line with the research of Wahyuni et al, which shows that obesity is more likely to experience PCOS, namely 50.5%. 6 Tavares and Barros state that the highest prevalence of patients with metabolic syndrome in each PCOS phenotype in Brazil has a BMI>30 kg/m 2 (obese).…”
Section: Resultsmentioning
confidence: 99%
“…From the results of the statistical test, it was concluded that there was a signifi cant relationship between insulin resistance and obesity (p <0.05) and there was a signifi cant relationship between insulin resistance and infertility (p <0.05). 7 The prevalence of insulin resistance for the normal BMI group (18.5-24.9 kg / m2), overweight (25-29.9 kg / m2) and obesity (≥30 kg / m2) is 19.3%, 56.2% and 78.2%, respectively. Being overweight and obese increases insulin resistance by OR 5.3 in overweight and OR 14.9 in obesity.…”
Section: Discussionmentioning
confidence: 96%
“…The result of the study show obesity and infertility can be affected by insulin resistance. 7 Based on this background the researcher wanted to fi nd out how the description of insulin resistance and BMI and the correlation of insulin resistance with BMI in obese female infertility.…”
Section: Introductionmentioning
confidence: 99%